Housing and Housing Finance - A Review of the Links to Economic Development and Poverty Reduction - John Doling; Paul Vandenberg; Jade Tolentino (Asian Development Bank (ADB), 2013)
The paper provides a review of the literature that links housing, housing finance, and economic development. The housing sector may support poverty reduction and inclusive growth in two general ways. First, housing construction contributes to economic output, creates employment, and generates a demand for materials and related services. Second, improved housing raises the standard of living of occupants. At the same time, housing purchases are costly for individuals, constituting the most valuable asset owned by most households and often requiring housing finance (mortgages) to allow for purchase. These links - between housing and the economy and between housing and housing finance - are explored in this review paper. It finds that the benefits of housing for individuals accrue in large part indirectly through better health, based on improved water and sanitation. Housing also generates large multiplier effects in terms of employment and output. Employment is created for both skilled and poorer, unskilled workers. The evidence also suggests that there is a symbiotic relationship between housing finance and financial sector development. Housing finance helps to develop the financial sector (contributing to economic growth) and is also helped by financial sector development.
hdl:11540/2302
Keywords: G21; O40; R21; 330; housing; finance; mortgages; inclusive growth